2022
DOI: 10.1007/s40257-022-00683-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Dupilumab in Adolescents with Moderate-to-Severe Atopic Dermatitis: Results Through Week 52 from a Phase III Open-Label Extension Trial (LIBERTY AD PED-OLE)

Abstract: Background For adolescent patients (aged ≥ 12 to < 18 years) with uncontrolled moderate-to-severe atopic dermatitis (AD), 16 weeks of treatment with dupilumab resulted in substantial clinical benefit compared with placebo, with an acceptable safety profile. However, long-term data on the approved dose regimens of dupilumab in adolescents with AD are lacking. Objectives This open-label extension study (LIBERTY AD PED-OLE, NCT02612454) reports the long-term safety, effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 27 publications
7
38
0
1
Order By: Relevance
“…A 52-week update of a multicentre Italian real-world experience on effectiveness and safety of dupilumab in adolescents with moderate-to-severe atopic dermatitis Dear Editor, Dupilumab, a fully human monoclonal antibody inhibiting signalling of both interleukin (IL)-4 and IL-13, was approved by European Medical Agency (EMA) in August 2019 for adolescents aged ≥12 years with moderate-to-severe atopic dermatitis (AD) after randomized clinical trials demonstrating long-term efficacy and safety. [1][2][3][4] Real-world studies, both at week 16 5 and week 32/52, 6,7 are rarely reported. We recently performed an Italian multicentre 16-week real-life study in 139 adolescents with moderate-to-severe AD treated with dupilumab.…”
mentioning
confidence: 99%
“…A 52-week update of a multicentre Italian real-world experience on effectiveness and safety of dupilumab in adolescents with moderate-to-severe atopic dermatitis Dear Editor, Dupilumab, a fully human monoclonal antibody inhibiting signalling of both interleukin (IL)-4 and IL-13, was approved by European Medical Agency (EMA) in August 2019 for adolescents aged ≥12 years with moderate-to-severe atopic dermatitis (AD) after randomized clinical trials demonstrating long-term efficacy and safety. [1][2][3][4] Real-world studies, both at week 16 5 and week 32/52, 6,7 are rarely reported. We recently performed an Italian multicentre 16-week real-life study in 139 adolescents with moderate-to-severe AD treated with dupilumab.…”
mentioning
confidence: 99%
“…65 Most of the adverse events were mild to moderate in severity as shown in previous open label extension studies of adults and adolescents with moderate to severe atopic dermatitis. 66,67 In our systematic review, most of our included patients reported mild or no adverse events, with ocular discomfort most frequently reported. 16,32,68 The infection risk in patients under dupilumab is also a concern.…”
Section: Discussionmentioning
confidence: 94%
“…Results from adolescent patients were recently published with findings relevant for a long-term safety profile consistent with the adult safety profile. Additionally, trial participants with clear/almost clear skin for 12 weeks were discontinued on DUPI with 56.7%, demonstrating recurrence and need to resume DUPI treatment to maintain AD control, which suggests a need to continue DUPI treatment to maintain efficacy [ 51 ]. With an excellent safety profile and high response rates, DUPI has become first line, when available, in refractory moderate–severe eczema.…”
Section: Biologicsmentioning
confidence: 99%